Notice of the Kers of Samuelston: in illustration of the previous deeds (Proceedings of the Society of Antiquaries of Scotland, 1862)
This article presents some information about the Ker family of Samuelston, particularly about how James Ker came to inherit Samuelston. The author speculates that there may have been a familial connection between James Ker and John Knox, but acknowledges that this would require further study to prove. Meeting notes for 15 February, 1858 are appended.